Implications of forest utilisation on bird conservation - Dranzoa, Christine (Journal of African Ornithology, 2000)
This paper gives a summary of the effect of selective logging upon forest bird communities. Some differences may exist from one region to another due to environmental as well as ecological factors. However, the general responses of bird communities to defined logging operations are predictable. A case study from Uganda’s Kibale National Park, is presented. Intensive mist-netting, counts and monitoring of breeding birds showed that species that are primarily adapted to exploiting forest edges, tree fall gaps and secondary habitats occurred and bred in large numbers in logged forest, but some species typical of forest interior were unable to adapt to logged forest. The long-term effects on the conservation of primary forest dependants are discussed.
Keywords: Forest utilisation; Bird conservation